Students' Metacognition Skills in the Context of Gender Stereotypes and Self-Confidence - Indah Earlyanti, Novi; Sandy, Amri (Jurnal Pedagogi dan Pembelajaran, 2025)
The inequality of perceptions based on gender stereotypes remains a crucial issue in education, as it can affect students' self-confidence and academic performance. On the other hand, metacognitive skills are believed to play an essential role in helping students overcome academic challenges and develop optimal self-confidence. This study aims to analyze the contribution of gender stereotypes to metacognitive skills and self-confidence, as well as examine the role of metacognitive skills in moderating the relationship between gender stereotypes and students' self-confidence. This research employed a quantitative approach supported by qualitative data through observations. The study involved a population of 307 students, with a purposive sampling technique selecting 102 respondents, measured using a standardized questionnaire. Data were analyzed using moderation regression techniques assisted by statistical software. The results showed that gender stereotypes did not have a significant effect on metacognitive skills or students' self-confidence. However, metacognitive skills were found to be positively and significantly related to self-confidence and did not moderate the relationship between gender stereotypes and self-confidence. These findings imply the importance of educational interventions based on metacognitive skills training to enhance students' self-confidence, regardless of the prevailing gender stereotype constructs in academic environments.